Profile of Osteomyelitis Patients Visiting the Orthopedic Clinic of Dr. Hasan Sadikin General Hospital, Indonesia, in 2017–2018 - Aditya Nugraha; Hermawan Nagar Rasyid; Hadyana Sukandar (Faculty of Medicine Universitas Padjadjaran, 2021)
Background: Osteomyelitis is an inflammatory process caused by microorganism infection that leads to bone destruction. Osteomyelitis may affect all bones, particularly long bones, and infects all ages. This disease is hard to diagnose and the treatment is complex due to the disease’s heterogenicity, pathophysiology, clinical presentation, and management. This study aimed to determine the profile of osteomyelitis inpatients and outpatients presented to the Orthopedic Clinic of Dr. Hasan Sadikin General Hospital Bandung, IndonesiaMethods: This was a descriptive cross-sectional study conducted from July to October 2019 using the total sampling method. Data were collected from the medical records of osteomyelitis inpatients and outpatients presented to the Orthopedic Clinic of Dr. Hasan Sadikin General Hospital Bandung, Indonesia from 2017–2018. Data were then analyzed descriptively and the results were presented in frequencies.Result: In total, 90 data were retrieved. Most of data presented male patients (n= 69, 76.7%) with the age range of 20–29 years old (24.4%). The majority of these patients experienced chronic onset of disease (94.4%) located on the tibia (51.1%), which was caused by a post-operative procedure (61.1%). The most common treatment was operative procedure without antibiotic beads (51.1%). Staphylococcus aureus was the common pathogens identified in these patients (22.2%).Conclusion: The majority of osteomyelitis patients are males in productive age with chronic onset of disease located on the tibia caused by a post-operative procedure. Staphylococcus aureus is the common pathogen involved and the most common treatment is an operative procedure without antibiotic beads.